Abundance, composition and fluxes of plastic debris and other macrolitter in urban runoff in a suburban catchment of Greater Paris. (15th March 2021) - Treilles, Robin; Gasperi, Johnny; Saad, Mohamed; Tramoy, Romain; Breton, Jérôme; Rabier, Alain; Tassin, Bruno
Highlights: Screened materials from stormwater of Paris suburb were collected for one year Plastic bags or films correspond to the most numerous items found in stormwater Plastic debris account for 53% of the mass of all anthropogenic waste The mean plastic debris concentration in stormwater is 41 mg/m 3 Separate sewer systems of Greater Paris may discharge 8-33 tons of plastic per year Abstract: Stormwater possibly represents a significant input for plastic debris in the environment; however, the quantification and composition of plastic debris and other macrolitter in stormwater are not available in literature and the amounts discharged into freshwater have been poorly investigated. To obtain a better understanding, the occurrence, abundance, and composition of the macrolitter in screened materials from stormwater were investigated at a small residential suburban catchment (Sucy-en-Brie, France) in Greater Paris. The macrolitter, particularly the plastic debris, was sorted, weighed, and classified based on the OSPAR methodology. On average, plastics accounted for at least 62% in number and for 53% of the mass of all the anthropogenic waste found in the screened materials. The most common items were plastic bags or films, crisp or sweet packets, cigarette butts, plastic fragments of unknown origin, garbage bags or garbage bag strings, foil wrappers, tampon applicators, plastic cups, and medical items such as bandages. Plastic debris concentrations in runoff water ranged between 7 and 134 mg/m 3 (i.e. 0.4–1.7 kg.yr −1 .ha −1 or 4.8–18.8 g.yr −1 .cap −1 ). When extrapolated to the Greater Paris area, the estimated amount of plastic debris discarded into the environment through untreated stormwater of separate sewer systems ranges from 8 to 33 tons.yr −1 . Graphical abstract: Image, graphical abstract